2020
DOI: 10.15446/revfacmed.v68n4.77430
|View full text |Cite
|
Sign up to set email alerts
|

Delirio en niños críticamente enfermos

Abstract: Este artículo fue aprobado para publicación en el v68n4 de la Revista de la Facultad de Medicina teniendo en cuenta los conceptos de los pares evaluadores y los cambios realizados por los autores según estos conceptos. Por lo tanto, se publica la versión preliminar del artículo para su consulta y citación provisional, pero debe aclararse que esta puede diferir del documento final, ya que no ha completado las etapas finales del proceso editorial (corrección de estilo, traducción y diagramación) y solo los títul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Other aspects that were not assessed in this study, but that were found in this comparative analysis with respect to the literature and that are considered of great importance for the study of this phenomenon, were its association with the use of physical restraints (Acosta‐Murillo, 2020; Kalvas & Harrison, 2020; Traube, Silver, Reeder, et al, 2017), severe disease (Kalvas & Harrison, 2020), blood transfusion (Acosta‐Murillo, 2020; Kalvas & Harrison, 2020), and the consequences of delirium in children related to increased medical costs due to delirium (Kalvas & Harrison, 2020), the increase in hospital mortality (Kalvas & Harrison, 2020; Torales & Navarro, 2019).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Other aspects that were not assessed in this study, but that were found in this comparative analysis with respect to the literature and that are considered of great importance for the study of this phenomenon, were its association with the use of physical restraints (Acosta‐Murillo, 2020; Kalvas & Harrison, 2020; Traube, Silver, Reeder, et al, 2017), severe disease (Kalvas & Harrison, 2020), blood transfusion (Acosta‐Murillo, 2020; Kalvas & Harrison, 2020), and the consequences of delirium in children related to increased medical costs due to delirium (Kalvas & Harrison, 2020), the increase in hospital mortality (Kalvas & Harrison, 2020; Torales & Navarro, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…These results highlight the importance of this phenomenon in this population, since its high presence is evident, which has consequences with a highly negative impact. This is due to the fact that it is considered an indicator of serious illness, and can generate higher mortality in critically ill children (Acosta‐Murillo, 2020), increasing the mortality rate by up to 20% (Torales & Navarro, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation